Gizi Anak Usia Sekolah Ceria Cegah Anemia Remaja Dengan Imbangan Asupan - Egy Sunanda Putra; Rusmimpong Rusmimpong; Alpari Nopindra (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT The high risk of anemia among female students at SMA Negeri 5 in Jambi City reflects a serious nutritional problem. Many students experience symptoms such as dizziness, weakness, nausea, and abdominal pain, which are directly related to anemia and nutritional imbalance. Dizziness and weakness can indicate iron deficiency, especially in adolescent girls. Complaints of nausea and heartburn indicate irregular eating patterns, which result in low intake of essential nutrients. Lack of knowledge about anemia and balanced nutrition is a major factor influencing unhealthy eating patterns among adolescents. To address this, educational interventions were conducted through education on anemia and balanced nutrition using Battle Quizzes and Kahoot! quizzes, the introduction of the